Correlation of enhanced thrombospondin-1 expression, TGF-β signalling and proteinuria in human type-2 diabetic nephropathy - Hohenstein, Bernd; Daniel, Christoph; Hausknecht, Birgit; Boehmer, Kirsten; Riess, Regine; Amann, Kerstin Ute; Hugo, Christian (Nephrology Dialysis Transplantation, 2008)
Background. Activation of the thrombospondin-1 (TSP-1)-TGF-β pathway by glucose and the relevance of TSP-1-dependent activation of TGF-β for renal matrix expansion, renal fibrosis and sclerosis have previously been demonstrated by our group in in vivo and in vitro studies. Design and methods. We investigated renal biopsies (n = 40) and clinical data (n = 30) of patients with diabetic nephropathy. Ten kidneys without evidence of renal disease served as controls. Glomerular and cortical expression of TSP-1, p-smad2/3, fibrosis and glomerular sclerosis (PAS) were assessed by immunhistochemical staining and related with clinical data. Results. Glomerular (g) and cortical (c) TSP-1 were increased during diabetic nephropathy (g: 2.62 ± 2.65; c: 4.5 ± 4.2) compared to controls (g: 0.67 ± 0.7; c: 1.5 ± 1.2). P-smad2/3 was significantly increased (g: 16.7 ± 12.9; c: 148.7 ± 92.8) compared to controls (g: 7.1 ± 3.6; c: 55 ± 25; P < 0.05). TSP-1 was coexpressed with p-smad2/3 as an indicator of TGF-β activation. TSP-1 correlated with enhanced tubulointerstitial p-smad2/3 positivity (r = 0.39 and r = 0.4, P < 0.05) and glomerular p-smad2/3 correlated with proteinuria (r = 0.35, P < 0.05). Conclusions. In summary, the present study suggests a functional activity of the TSP-1/TGF-β axis, especially in the tubulointerstitium of patients with diabetic nephropathy. The positive correlation of glomerular p-smad2/3 positivity with proteinuria further supports the importance of the TSP-1/TGF-β system as a relevant mechanism for progression of human type-2 diabetic nephropathy. © The Author [2008].
Created from Fastlane, Scopus look-up
Keywords: Diabetic nephropathy; Proteinuria; TGF-β; TSP-1; Tubulointerstitium